GEOMETRIC CHARACTERIZATION OF LOW-VELOCITY IMPACT DAMAGE IN CARBON-FIBRE-REINFORCED POLYMER LAMINATES: A REVIEW OF METHODS - Pedan, Yevhen (Problems of Friction and Wear, 2026)
This review considers methods for describing residual surface geometry after low-velocity impact in carbon-fibre-reinforced polymer (CFRP) laminates. The main focus is the diagnostic relationship between surface parameters and internal damage, especially delamination associated with barely visible impact damage (BVID). The analysed parameters include maximum indentation depth, damaged-area size, equivalent diameter, indentation volume, profile shape, surface curvature and time-dependent indentation recovery. Contact measurements, optical profilometry, three-dimensional scanning, digital image correlation, automated visual detection and hybrid nondestructive evaluation schemes are compared. The review shows that surface geometry is a useful diagnostic characteristic but cannot be interpreted as a complete representation of internal damage. Reliable assessment requires accounting for laminate thickness, stacking sequence, impactor geometry, impact energy, boundary conditions, time after impact, environmental factors and NDE verification. The most promising direction is the integration of 3D surface profiling, nondestructive evaluation and machine-learning models for predicting internal damage and residual compression-after-impact strength.